Community Based Tourism Management at Pinge Village, Tabanan Regency, Bali - Gde Agus Jaya Sadguna, Anak Agung Ayu Ngurah Harmini (European Journal of Sustainable Development, 2017)
The demand of something different has driven tourism destination to make new attractions to accommodate various needs of tourists. The idea of presenting authentic local attraction has given local people something to expect from tourism. Thus the idea of community based tourism emerges. This research was conducted at Pinge Village in Tabanan Regency; focusing on the management of the Pinge Village governing body, which consists of the local people themselves. The purpose of this research is to identify and illustrate the role of the governing body for the benefit of the local people. The data collection is done by observation, interview, and literature review. The analysis technique used is descriptive qualitative research. The result is that the governing body is responsible for managing the village’s attraction, activities, and facilities, namely trekking, performing arts, farming activities, cooking class, and home stay. These attractions, activities and facilities are either owned personally by the villagers or owned by the village. The aim of the governing body is to make the people and village prosperous. Keywords: Community Based Tourism, management, Pinge Village, governing body, alternative tourism